Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.1 Use Properties of Exponents - 5.1 Exercises - Skill Practice - Page 334: 48



Work Step by Step

Since, $\dfrac{a^m}{a^n}=a^m \times \dfrac{1}{a^n}$ Also, $a^{-n}=\dfrac{1}{a^n}$ Thus, $a^m \dfrac{1}{a^n}=a^m a^{-n}$ ...(1) Now, we need to use the product of powers property. $a^{m}a^{-n}=a^{m-n}$ Equation (1) becomes: $a^m \dfrac{1}{a^n}=a^m a^{-n}=a^{m-n}$ This gives: $\dfrac{a^m}{a^n}=a^{m-n}$ Hence, the result has been verified.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.